ANALYZE THE INTENTION TO VISIT TOURISM DESTINATION (CASE STUDY: VALENTINE HILLS TOMOHON) - Kasim, Gabriella Angely; Massie, James D. D.; Arie, Fitty Valdi (Universitas Sam Ratulangi, 2019)
Abstract: Nowadays, along with globalization and technological development as well as online transportation, people more easy to going tourism destination and so many tourism destination can be selection. The aim of this study is to analyze the intention to visit tourism destination with case study in Valentine Hills Tomohon measure by atmospheric, enjoyment, escape, excellence and economic value. This research is quantitative type of research, and the data analysis methods used are multiple linear regression. The population of this research is peoples who have visiting Valentine Hills Tomohon, questionnaire is used to collect the data where the sample size is 100 respondents. The result of this research found that atmospheric, enjoyment, escape, excellence, and economic value simultaneously influence the intention to visit and partially there are two dimensions that have a significant influence on intention to visit are enjoyment and economic value while atmospheric, escape, and excellence have no significant effect on intention to visit. The recommendation of this study can be used as a reference for the development and deepening of knowledge management marketing.ÂÂKeywords: intention to visit, tourism, valentine hills tomohon